Take-Home Naloxone for the Emergency Interim Management of Opioid Overdose: The Public Health Application of an Emergency Medicine - Strang, John; McDonald, Rebecca; Campbell, Gabrielle; Degenhardt, Louisa; Nielsen, Suzanne; Ritter, Alison; Dale, Ola (Drugs (New York, N.Y.), 2019)
Naloxone is a well-established essential medicine for the treatment of life-threatening heroin/opioid overdose in emergency medicine. Over two decades, the concept of ‘take-home naloxone’ has evolved, comprising pre-provision of an emergency supply to laypersons likely to witness an opioid overdose (e.g. peers and family members of people who use opioids as well as non-medical personnel), with the recommendation to administer the naloxone to the overdose victim as interim care while awaiting an ambulance. There is an urgent need for more widespread naloxone access considering the growing problem of opioid overdose deaths, accounting for more than 100,000 deaths worldwide annually. Rises in mortality are particularly sharp in North America, where the ongoing prescription opioid problem is now overlaid with a rapid growth in overdose deaths from heroin and illicit fentanyl. Using opioids alone is dangerous, and the mortality risk is clustered at certain times and contexts, including on prison release and discharge from hospital and residential care. The provision of take-home naloxone has required the introduction of new legislation and new naloxone products. These include pre-filled syringes and auto-injectors and, crucially, new concentrated nasal sprays (four formulations recently approved in different countries) with speed of onset comparable to intramuscular naloxone and relative bioavailability of approximately 40–50%. Choosing the right naloxone dose in the fentanyl era is a matter of ongoing debate, but the safety margin of the approved nasal sprays is superior to improvised nasal kits. New legislation in different countries permits over-the-counter sales or other prescription-free methods of provision. However, access remains uneven with take-home naloxone still not provided in many countries and communities, and with ongoing barriers contributing to implementation inertia. Take-home naloxone is an important component of the response to the global overdose problem, but greater commitment to implementation will be essential, alongside improved affordable products, if a greater impact is to be achieved.